The dark side of the moon [compact disc] - Waters, Roger (Pink Floyd Music Ltd., 2023)
Originally released in 1973, this complex, often psychedelic music works very well because Pink Floyd doesn't rush anything. The songs are mainly slow to mid-tempo, with attention paid throughout to musical texture and mood.